The Relationship Between Body Mass Index and Breast Volume on Mammography Examination - Nur Azizah Sultan, Salsabila; Aurora, Habiba; Fahmi Fahanani, Agwin (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2023)
Breast cancer is the most common type of cancer suffered by women worldwide. The development and incidence of breast cancer is influenced by various risk factors, one of which is breast volume. The amount of breast volume is influenced by several factors such as genetics, demographics, reproduction, lifestyle, and Body Mass Index (BMI). This study aims to determine the relationship between Body Mass Index and breast volume of research subjects at RSUD Dr. Saiful Anwar Malang, East Java. This type of research is observational analytic with a cross-sectional study approach and analysis using Kruskal Wallis test, the Mann Whitney test, and Spearman correlation test. Based on the Kruskal Wallis test BMI-left breast volume, the sig value obtained was 0.020 (sig < 0.05) while in the analysis of BMI-right breast volume the sig value obtained was 0.083 (sig > 0.05). Follow-up analysis using the Mann-Whitney BMI test-left breast volume showed significant results in the normal-overweight (p=0.050) and normal-obese (p=0.007) BMI groups. While the BMI-volume analysis of the right breast showed significant results only in the normal-obese BMI group (p = 0.044). Spearman correlation test of BMI-left breast volume obtained sig = 0.000 and r = 0.603. While the Spearman test of BMI-right breast volume obtained sig = 0.004 and r = 0.511. This study concludes that there is a significant relationship between BMI and breast volume which is positive with a fairly strong correlation strength.